Genetic variability and character association in bread wheat (Triticum aestivum) - MEENA, H S; KUMAR, DINESH; PRASAD, S RAJENDRA (The Indian Journal of Agricultural Sciences, 2014)
Forty seven released varieties of common bread wheat (Triticum aestivum L.) were evaluated during rabi 2007-08 to 2010-11 for four years under irrigated conditions at Directorate of Seed Research, Mau. Analysis of variance on 12 quantitative characters was carried out and pooled analysis was conducted over the seasons. The mean, range, phenotypic, genotypic and environmental variance, genotypic and phenotypic coefficient of variation, heritability in broad sense and genetic advance were calculated. Path coefficient analysis was carried out using correlation coefficients to establish the inter-relationship and direct and indirect contributions of component traits towards grain yield. Analysis of variance revealed the considerable amount of genetic variability in genotypes for all the traits. High genetic advance (GA) coupled with moderate to high heritability for grains/ spike and 1000-seed weight indicated the effectiveness of selection for these traits. Number of grains/spikelet, grain yield/spike and effective tillers/m2 were positively associated with grain yield. Similarly, effective tillers/m2, number of grains/spike and grain yield/spike had higher phenotypic and genotypic direct effects on grain yield/m2, revealing that indirect selection for these traits would be effective in improving the grain yield. The higher direct and indirect contribution of grains/spike, tillers/m2, 1000-seed weight, spikelets/spike and grains/spikelet towards total grain yield would be of great use for indirect selection for yield improvement.